Special sensitivity? : the white-collar offender in prison - Stadler, William Andrew, 1978- (Criminal justice (LFB Scholarly Publishing LLC), 2012)
Despite recent increases in incarceration for white-collar offenders, little is known about their prison experiences or how they adjust to imprisonment. In the justice system a view has prevailed that white-collar offenders have a?special sensitivity? to imprisonment?that they are more susceptible to the pains of prison. Stadler explores this view to determine how white-collar inmates adjust to life in prison and whether they do so differently than street offenders. Evidence suggests that white-collar inmates are no more likely to experience negative prison adjustment than street offenders, a.